Educational intervention to improve knowledge, attitude and practice of pharmacovigilance among nursing staff in tertiary care hospital - Hingorani, Sadhana; Mehta, Chaitali; Gajera, Paresh; Srivastava, S. K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The present study was planned to assess the knowledge, attitude and practice among nursing staff and to evaluate the effect of educational intervention. Methods: The questionnaire related with knowledge, attitude and practice (KAP) were given to nursing staff before and after the educational intervention in a tertiary care hospital. The data obtained were subjected to statistical analysis. Results: The training given in different sessions has improved KAP among nursing staff. Ninety six percent of them responded correctly regarding who can report ADR as compared to pre training session (69%). Regarding pharmacovigilance as purpose of safe use of medicines was responded by 71% after training as compared to 54% before training. In questions related to PvPI, 94% of nursing staff responded correctly about the scale to be used for causality assessment in comparison to 79% before training. Majority of them were of opinion that only unknown and serious ADR should be reported whereas after training they answered that all the ADR should be reported. A significant improvement has been noticed in questions related to attitude and practice. Conclusions: The educational intervention to improve KAP among nursing staff has resulted in significant improvement.